2013
DOI: 10.1149/05037.0087ecst
|View full text |Cite
|
Sign up to set email alerts
|

(Invited) The Effects of Confinement and Coulomb Blockade on the Transport in Ensembles of Si Quantum Dots

Abstract: In our previous works we tried to provide a framework for the basic transport mechanisms in ensembles of Si quantum dots. In the present work we try to confirm that the quantum confinement and Coulomb blockade are present in the ensembles and to evaluate their effect on the electrical transport in the ensembles. We conclude that the most conspicuous influence of those nano phenomena on the transport is found in the close vicinity of the conductivity percolation threshold of the ensembles. .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 36 publications
3
13
0
Order By: Relevance
“…Hence, these measurements confirmed the existence of the QC and CB effects up to the percolation threshold of clusters of touching NCs. This behavior becomes also evident from measurements near x c where a scenario that is quite similar to the one found in the STS measurements in revealing a voltage gap that may be associated with the presence of QC and CB effects [3,17]. Above x c we could easily measure the electrical conductivity and thus, the two conspicuous features that our samples provide are the strong PL (with a peak at x d ) and the rise in the electrical conductivity (in accordance with percolation theory [16]) in the high density regime.…”
Section: The Presence Of Quantum Confinement and Coulomb Blockade Phesupporting
confidence: 67%
“…Hence, these measurements confirmed the existence of the QC and CB effects up to the percolation threshold of clusters of touching NCs. This behavior becomes also evident from measurements near x c where a scenario that is quite similar to the one found in the STS measurements in revealing a voltage gap that may be associated with the presence of QC and CB effects [3,17]. Above x c we could easily measure the electrical conductivity and thus, the two conspicuous features that our samples provide are the strong PL (with a peak at x d ) and the rise in the electrical conductivity (in accordance with percolation theory [16]) in the high density regime.…”
Section: The Presence Of Quantum Confinement and Coulomb Blockade Phesupporting
confidence: 67%
“…In the preset work, we studied σ(t), the time response of the conductivity to external time-dependent electrical or optical excitations, both during and after these excitations. Our study involved systems for which the QC, CB, and CS effects have been well demonstrated in many works by others [ 12 , 18 , 21 ] and by us [ 9 , 16 , 22 ]. Here, however, we focus on the changes in σ(t) with the variation in the basic parameter that determines these effects, i.e., the diameter of the nanoparticles, d .…”
Section: Introductionmentioning
confidence: 89%
“…To ensure the formation of Si NCs in the films, the slide samples were annealed at 1100–1200 °C in a N 2 atmosphere for about an hour. In particular, for an annealing temperature T a ≥ 1150 °C, the Si phase of the films practically consists only of NCs [ 16 , 75 , 86 , 87 ]. This conclusion was derived from our Raman [ 10 , 16 ] and HRTEM [ 75 , 86 ] measurements.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations